IMPROVING STUDENTS’ SPEAKING ABILITY THROUGH TWO STAY – TWO STRAY OF FPBS IKIP MATARAM - Dedi Sumarsono; Abdul Kadir Bagis (Universitas Pendidikan Mandalika, 2014)
This research is aimed at knowing whether students’ speaking ability can be improved by using Two Stay - Two Stray and what are the strengths and weaknesses of Two Stay - Two Stray in teaching speaking in the second semester students of FPBS IKIP Mataram in the academic years of 2013/2014. This research uses Classroom Action Research (CAR) which is taken from Kemmis and McTanggart’s design; it consists of 2 cycles. Every cycle consists of four phases those are: planning, acting, observing, and reflecting. The subject of this research is the students in IId of FPBS IKIP Mataram. Field note, questionnaire, and test are used in collecting the data. There are three tests used in this research, they are: pre-test, post-test 1, and post-test 2 with the standard of students’ successful was 65. The findings of the research showed that (1) The students’ speaking ability improved; (2) Related to the field note results showed that the students were more confident and enthusiast in speaking. It can be seen from their participation in the class, in the conversation, and their performance in group work; and (3) Related to the questionnaire result, it is proved that the response of the students toward Two Stay – Two Stray in teaching speaking is 96%. Based on all those findings, it can be concluded that the application of Two Stay - Two Stray can improve the students’ speaking ability.